2022
DOI: 10.3389/fphar.2022.1039857
|View full text |Cite
|
Sign up to set email alerts
|

A risk model developed based on necroptosis to assess progression for ischemic cardiomyopathy and identify possible therapeutic drugs

Abstract: Object: Ischemic cardiomyopathy (ICM), with high morbidity and mortality, is the most common cause of heart failure. Cardiovascular remodeling secondary to chronic myocardial ischemia is the main cause of its progression. A recently identified type of programmed cell death called necroptosis is crucial in the development of various cardiovascular diseases. However, the function role of necroptosis in cardiac remodeling of ICM has not been elucidated. Our study aimed to screen for genes associated with necropto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…TNFSF10 belongs to a family of tumor necrosis factor (TNF) ligands that induce apoptosis by binding to their receptors and triggering the activation of MAPK8/JNK, caspase 8 and caspase 3 ( 53 ). It was reported that TNFSF10 could be a marker of necroptosis in various diseases, such as ischemic cardiomyopathy and cancers ( 54 , 55 ). This study is the first to identify TNFSF10 as a diagnostic marker of necroptosis in PCOS, and its specific function in the development of PCOS needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…TNFSF10 belongs to a family of tumor necrosis factor (TNF) ligands that induce apoptosis by binding to their receptors and triggering the activation of MAPK8/JNK, caspase 8 and caspase 3 ( 53 ). It was reported that TNFSF10 could be a marker of necroptosis in various diseases, such as ischemic cardiomyopathy and cancers ( 54 , 55 ). This study is the first to identify TNFSF10 as a diagnostic marker of necroptosis in PCOS, and its specific function in the development of PCOS needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Necroptosis is a novel type of programmed cell death that has been extensively investigated for its diagnostic and prognostic potential in various illnesses, such as ischemic cardiomyopathy [ 44 ], Stanford types A aortic dissection [ 45 ], and cutaneous melanoma [ 46 ]. In recent years, growing researchers have actively mined and analyzed data from GEO or other databases to find potential molecular markers for PE diagnosis and treatment.…”
Section: Discussionmentioning
confidence: 99%